PENGETAHUAN, DUKUNGAN SUAMI DAN TINGKAT PARTISIPASI IBU HAMIL DALAM COUPLE PREGNANCY CLASS - Emilda Armika Vianti; Sri Mumpuni Yuniarsih (Universitas Pesantren Tinggi Darul Ulum, 2022)
In poor countries, around 25-30% of deaths of childbearing age are caused by things related to pregnancy and childbirth. The Indonesian government has made efforts to accelerate the reduction of MMR by increasing knowledge and changing the behavior of mothers and families so that it is hoped that awareness of the importance of health during pregnancy will increase. The program organized by the Ministry of Health to support this step is the class for pregnant women. The purpose of this study was to describe the level of knowledge of pregnant women, the support of husbands and the level of participation in the pair pregnancy class program. Couple Class. This research is a descriptive study with a sampling technique using purposive sampling. In this study most of the husbands had good knowledge (62%), participated (62%) and supportive husbands (75%). This was made possible because the participants in this maternity class had been determined from the start that the mother had to attend with her partner and it was recommended by the village midwife. Husband's support is also the most important factor in the participation of mothers in pregnancy classes. Therefore the pregnancy class which involves these couples must continue to be socialized and it is hoped that it can be accommodated by the Health Service so that its implementation can be carried out in all health centers in Indonesia. Keywords: Pregnancy Class, Motivation, Couple Class.